Transcriptomic Resilience of the Montipora digitata Holobiont to Low pH - González-Pech, Raúl A.; Vargas, Sergio; Francis, Warren R.; Wörheide, Gert (Frontiers in Marine Science, 2017)
Ocean acidification is considered as one of the major threats for coral reefs at a global scale. Marine calcifying organisms, including stony corals, are expected to be the most affected by the predicted decrease of the surface water pH at the end of the century. The severity of the impacts on coral reefs remains as a matter of controversy. Although previous studies have explored the physiological response of stony corals to changes in pH, the response of the holobiont (i.e., the coral itself plus its symbionts) remains largely unexplored. In the present study, we assessed the changes in overall gene expression of the coral Montipora digitata and its microalgal symbionts after a short (3 days) and a longer (42 days) exposure to low pH (7.6). The short-term exposure to low pH caused small differences in the expression level of the host, impacting mostly genes associated with stress response in other scleractinians. Longer exposure to low pH resulted in no significant changes in gene expression of treated vs. control coral hosts. Gene expression in the eukaryotic symbionts remained unaltered at both exposure times. Our findings suggest resilience, in terms of gene expression, of the M. digitata holobiont to pH decrease, as well as capability to acclimatize to extended periods of exposure to low pH.